Spectrophotometric Method for the Determination of Drugs Containing Phenol Group by Using 2, 4- Dinitrophenylhydrazine - Padmarajaiah Nagaraja; Ashwinee Kumar Shrestha (E-Journal of Chemistry)
A spectrophotometric method has been proposed for the determination of four phenolic drugs; salbutamol, ritodrine, amoxicillin and isoxsuprine. The method is based on the oxidation of 2, 4- dinitrophenyl-hydrazine and coupling of the oxidized product with drugs to give intensely colored chromogen. Under the proposed optimum condition, beer’s law was obeyed in the concentration range of 2.5-17, 2-29, 4-33 and 5-30 μg/mL for salbutamol, ritodrine, amoxicillin and isoxsuprine respectively. The limit of detection (LOD) and limit of quantification (LOQ) were 0.2, 0.83, 0.09, 0.84 μg/mL and 0.66, 2.79, 0.3 and 2.81 μg/mL in the same order. No interference was observed from common pharmaceutical adjuvants. The ringbom plots and low relative standard deviation assert the applicability of this method. The suggested method was further applied for the determinations of drugs in commercial pharmaceutical dosage forms, which was compared statistically with reference methods by means of t- test and F- test and were found not to differ significantly at 95% confidence level. The procedure is characterized by its simplicity with accuracy and precision.